Pembangunan Karakter Dalam Pelaksanaan Kegiatan Keagamaan di Lingkungan Sekolah - Ainun Syahrani; Dama Calya Lardianata; Zahra Aisyah Putri; Abdul Fadhil (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This research aims to show the extent to which Islamic Religious Education (PAI) contributes to the development of tolerant student character at Jakarta State University (UNJ). This research uses a qualitative approach using library research methods (library study). to analyze character development in the practice of religious activities in the school environment. The research results show that strong character development occurs through religious practices at school which strengthen students' character. This research concludes that although Islamic religious education has a very important role in forming a tolerant character, it needs to be supported by various other efforts from both the school and the students themselves.